Etnoconhecimento Sateré Mawé e a influência de fatores ambientais e antrópicos na distribuição de espécies florestais de interesse da etnia - Aguiar, Olivia Beatriz Moraes Dias de (Instituto Nacional de Pesquisas da Amazônia - INPA, 2018)
Indigenous peoples have managed Amazonian forests for millennia, enhancing the propagation and growth of useful and domesticated species. The distribution of forest species is related to environmental and evolutionary factors, as well as pre-Columbian and recent histories of use, occupation and management. The Sateré-Mawé ethnic group traditionally manage forests in the Amazonas-Madeira-Tapajós interfluve. The main objective of this study was to evaluate the use, management and distribution of 12 important forest species in the Andirá-Marau territory. We worked with the seed collectors of the priority species and analysed how the abundance and basal area of domesticated and non domesticated species are distributed in the lower Andirá river, considering environmental and anthropogenic attributes. For a better understanding of the results, we studied the indigenous knowledge about the uses and management of the priority species and the soils around the communities. We found that the Sateré-Mawé are actively managing the forests; their management practices were classified into nine categories that lead to a process of forest domestication. Six ethnosoils were described by easily perceived attributes, such as colour, texture and vegetation. The assemblage of the 12 priority species is more abundant in regions closer to the communities, in soils with higher phosphorus content, higher amounts of charcoal and lower iron content.The distribution of the domesticated species was explained by attributes sensitive to anthropogenic modifications, such as increase of charcoal in the soil, higher pH and sum of bases. Non-domesticated populations had higher abundances at more elevated altitudes, in soils with higher phosphorus and iron content, and higher basal area in more acidic soils. Combining modern scientific study with indigenous knowledge enabled a better interpretation of the results, highlighting the importance of this dialogue to increase the understanding of Amazonian forests and design strategies for productive systems that are more resilient and suitable for local realities.
Keywords: manejo florestal indígena; Florestas antrópicas; Etnoedafologia